High sensitivity sensing of nitroaromatic explosive vapors based on polytriphenylamines with AIE‐active tetraphenylethylene side groups. Issue 15 (3rd April 2015) - Dong, Wenyue; Pan, Yuyu; Fritsch, Martin; Scherf, Ullrich
ABSTRACT Two polytriphenylamines (PTPAs) (P1 and P2) with aggregation induced emission (AIE)‐active tetraphenylethylene side groups have been designed and successfully synthesized. Both polymers only faintly emit in dilute solution but show strong emission in aggregated state, meaning that they are AIE‐active. The detection of 1, 3, 5‐trinitrobenzene (TNB) vapors has been investigated by photoluminescence (PL) quenching in polymer films. High solid state quantum yields and donor‐acceptor interactions of the electron‐rich PTPA chains with the TNB analyte, hereby, induce a high sensing sensitivity, both for P1 and P2 films towards TNB vapor. Contacting thin P1 and P2 films with saturated TNB vapor, the PL intensity was quenched by 85% for P1 and 89% for P2 within 600 s, respectively. The sensing process is reversible, >90% of the PL is recovered, also after repeated cycling. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 53, 1753–1761